Proceedings of the inauguration of the international year of the family and the National Assembly on the family, February 8, 1994, Santi Maitree Building, Government House : report (Office of the National Commission on Women's Affairs, Office of the Permanent Secretary, Office of the Prime Minister : UNICEF, 1994)
Chapters chiefly on Thai family affairs.